(untitled) - Passikoff, Robert (Hoboken, N.J., 2006)
"Predicting Market Success has come at the right time for major companies. The value of understanding the dimensions of your brand's unique appeal and strength of preference is indispensable for brand strategy today. This book is well worth your time."
Keywords: Customer loyalty,Khách hàng trung thành